QORAQALPOQ TILIDAGI SINONIM FRAZEMALARNING BADIIY ADABIYOTDAGI USLUBIY XUSUSIYATLARI - Xaytbayev, O.A. (SCIENCE and SOCIETY, 2024)
In this article, Karakalpak writers masterfully use phrases in the language to enhance the emotional expressiveness of the work, reflecting certain character traits of the hero. At the same time, the examples show the skillful use of sages to achieve expressiveness even by making changes in their content, their reformulation.